Lymphocyte subpopulations in patients with acute brucellosis - Çelik, Ilhami; Akbulut, H. Handan (My University, 2005)
The aim of this work was to evaluate changes in lymphocyte subpopulations, especially helper and cytotoxic T cells, in acute brucellosis patients undergoing treatment. Forty-three acute brucellosis patients were included in the study. Twenty healthy subjects served as controls. Total lymphocytes and the CD3+, CD4+, CD8+, CD19+ and CD (16+56)+ subpopulations were counted by two-color flow cytometric analysis. The CD4+ counts in patients before and after treatment were not statistically different (p = 0.7), but healthy subjects had significantly more of these cells (p = 0.001 and p = 0.001 compared to pre- and post-treatment patients, respectively). The CD8+ counts in acute brucellosis patients decreased after treatment (p = 0.004), but remained higher in both pre- and post-treatment samples than in healthy subjects (p = 0.001 and p = 0.01 respectively). Neither the total leukocyte counts nor the numbers of cells in any subpopulation correlated with blood culture results (positive or negative). No statistically significant differences in the patients' CD4+ T cell counts were observed between the pre-and post-treatment periods, and the count was higher in healthy subjects. Counts of CD8+ T cells increased in acute brucellosis patients, and although they decreased after treatment they remained higher than in the controls. In view of this increase, it was concluded that CD8+ T cells could be the major component in immunity against brucellosis. © Tübi?tak.
Keywords: Brucellosis; Lymphocyte subpopulations; Treatment